Advances in Faba Bean Genetics and Genomics - O'Sullivan, Donal M.; Angra, Deepti (Frontiers in Genetics, 2016)
Vicia faba L, is a globally important grain legume whose main centres of diversity are the Fertile Crescent and Mediterranean basin. Because of its small number (six) of exceptionally large and easily observed chromosomes it became a model species for plant cytogenetics the 70s and 80s. It is somewhat ironic therefore, that the emergence of more genomically tractable model plant species such as Arabidopsis and Medicago coincided with a marked decline in genome research on the formerly favoured plant cytogenetic model. Thus, as ever higher density molecular marker coverage and dense genetic and even complete genome sequence maps of key crop and model species emerged through the 1990s and early 2000s, genetic and genome knowledge of Vicia faba lagged far behind other grain legumes such as soybean, common bean and pea. However, cheap sequencing technologies have stimulated the production of deep transcriptome coverage from several tissue types and numerous distinct cultivars in recent years. This has permitted the reconstruction of the faba bean meta-transcriptome and has fuelled development of extensive sets of Simple Sequence Repeat and Single Nucleotide Polymorphism (SNP) markers. Genetics of faba bean stretches back to the 1930s, but it was not until 1993 that DNA markers were used to construct genetic maps. A series of Random Amplified Polymorphic DNA-based genetic studies mainly targeted at quantitative loci underlying resistance to a series of biotic and abiotic stresses were conducted during the 1990’s and early 2000s. More recently, SNP-based genetic maps have permitted chromosome intervals of interest to be aligned to collinear segments of sequenced legume genomes such as the model legume Medicago truncatula, which in turn opens up the possibility for hypotheses on gene content, order and function to be translated from model to crop. Some examples of where knowledge of gene content and function have already been productively exploited are discussed. The bottleneck in associating genes and their functions has therefore moved from locating gene candidates to validating their function and the last part of this review covers mutagenesis and genetic transformation, two complementary routes to validating gene function and unlocking novel trait variation for the improvement.